The economics of retail payments: theory and practice - Chakravorti, Sujit (Henry Stewart Talks, 2010)
Retail payment systems, Production side of payments, Move to electronic payments, Payment taxonomy, Cash transactions, Growth of debit card transactions, A study of cash substitution, Payment cards, Anti-trust scrutiny, Costs and benefits of electronic payments, Payment card network transfers, Sharing of surplus among participants and consumers, Externality, Honor-all-cards rules, Government intervention of payment card networks, Case studies: Australia, Spain, Innovation